Możliwość bezpośredniego stosowania dyrektywy Unii Europejskiej w polskim porządku prawnym na przykładzie przepisów dotyczących interoperacyjności systemu kolei - Wiśniewska, Justyna (Kwartalnik Prawa Publicznego, 2016)
Article “The possibility of direct application of the European Union Directive in the Polish legal system on the example of railway system interoperability regulations” is an attempt to find a legal solution to the situation where the provisions implementing the directive on specific issues relating to both external and public administrations are repealed and are not replaced by new ones. Directive 2008/57/EC of the European Parliament and of the European Council on the interoperability of the rail system in the Community has been implemented in the Polish legal system by the Interoperability Regulation. The Regulation currently in force was issued on May 12, 2017 and has been in force since May 13, 2017. The previous Regulation was waived on April 20, 2017. The legislature has not issued any transitional provisions. The consequence of the above was a gap in the Polish legal order regarding rail interoperability. This caused that rail market operators for 23 days had no basis to apply for the EC verification procedure and consequently to apply for subsystems: infrastructure, power, control – trackside equipment, control – on-board equipment and rolling stock approval for vehicles complying and not complying with the Technical Interoperability Specifications. The activity of the competent public administration was also limited – there was no basis in the Polish legal order to issue authorizations for admission to service for the abovementioned subsystems. With this in mind, the author of this article carried out a legal analysis of the possibility of applying directly the provisions of the aforementioned Directive, confirming in summary the legality of the solution in question.